Lack of induction of neuroretinal cell proliferation by Rous sarcoma virus variants that carry the c-src gene. - Iba, H (1985)
Expression of p60v-src of Rous sarcoma virus in cultured chicken embryo neuroretinal cells was previously shown to result in the transformation and sustained proliferation of normally quiescent cell populations. We show here that Rous sarcoma virus variants that encode p60c-src, the cellular homolog of p60v-src, lack the ability to induce morphological transformation and cell proliferation of cultured neuroretinal cells. Neuroretinal cells infected with c-src-containing viruses, however, possess no less p60 protein kinase activity assayed in the immune complex than those infected with the transformation-defective Rous sarcoma virus mutants PA101 or PA104, which do stimulate the growth of these cells.